2021
DOI: 10.1186/s43058-021-00203-z
|View full text |Cite
|
Sign up to set email alerts
|

Reflective writing: a tool to support continuous learning and improved effectiveness in implementation facilitators

Abstract: Background Implementation facilitators support the adoption of evidence-based practices and other improvement efforts in complex healthcare settings. Facilitators are trained to develop essential facilitation skills and facilitator effectiveness is typically evaluated post-implementation, but little is known about how facilitators apply and adapt didactic knowledge after training, or how learning and refining experiential knowledge occurs during the facilitation process. We propose the use of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…In our study, this was supported by encouraging CE facilitators' reflection on the process and key issues that emerged in each CE session, which provided a space to record feedback from communities, helped to strengthen facilitators' engagement with activities and supported monitoring and evaluation of the program. Facilitator reflections has been used in quality improvement initiatives to promote buy-in and motivation as well as provide the time and structure to reflect on potential adaptations to improve engagement [20,21].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…In our study, this was supported by encouraging CE facilitators' reflection on the process and key issues that emerged in each CE session, which provided a space to record feedback from communities, helped to strengthen facilitators' engagement with activities and supported monitoring and evaluation of the program. Facilitator reflections has been used in quality improvement initiatives to promote buy-in and motivation as well as provide the time and structure to reflect on potential adaptations to improve engagement [20,21].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…One study (3%) was not clear on this aspect 32 . In the majority of studies (55%, 20/36), facilitators were appointed, assigned, or employed in that role, 13,14,22,23,25,26,30,31,33,36,39–42,44,45,47,49,50 while others (11%, 4/36) had facilitators who self-selected or expressed their interest in the role 20,38,48,52 . A small number of studies (11%, 4/36) examined whether a position (e.g., middle manager) had facilitator roles and functions, 21,28,29,35 a few had a mix of volunteers and appointed facilitators (6%, 2/36), 5,24 while the remainder (17%, 6/36) did not specify how this role was assumed 27,32,34,43,46,51 Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…After the discussion, participants were asked to perform reflective journal writing based on their experiences and perceptions. Olmos-Ochoa et al 9 reported that reflective writing is said to encourage a writer to learn from an event, because it necessitates focused and analytical thinking.…”
Section: Methodsmentioning
confidence: 99%